ANALISIS RESPON PENAWARAN KEDELAI DI INDONESIA - Muhammad Firdaus (STIE Mandala Jember, 2014)
Soybean is a major cropafter rice and maize. Most soybean sare used as raw materials of tempeh and tofu. Indonesian soybean production is always less than the demand. This study aims to: (1) to determine the factors that affect the response of soybean a cre age in Indonesia, (2) to determine the factors that affect the response of soybean productivity in Indonesia, and (3) to determine the most dominant factors that affect to soybean supply response. The data used are secondary data, iethe data of national soybean 1979-2013 period. This study uses the Partial Adjustment Model by Nerlove. The results showed that: (1) Lag soybean prices and dum my base price does not significantly affect soybean acre age. Soybean soybean acre age only significantly affected by soybean acre age lag. (2) Lag productivity and lag soybean prices have a significant effect on the productivity of soybean, soybean acreage where as no significant effect. (3) Response offers more influenced by the response of productivity than the response area.